Homonymous hemiatrophy of ganglion cell layer from retrochiasmal lesions in the visual pathway. (21st January 2020) - Mühlemann, Fabian; Grabe, Hilary; Fok, Anthony; Wagner, Franca; Brügger, Dominik; Sheldon, Claire A.; Abegg, Mathias
Abstract : Objective: To determine the temporal evolution, morphology, and frequency of macular ganglion cell atrophy in patients with retrochiasmal lesions of the visual pathway. Methods: In a consecutive retrospective case series, we identified 47 patients with homonymous hemianopia and accessible macular optical coherence tomography scans. We estimated the time of lesion onset and the location of the lesion within the afferent visual pathway. Using semiautomatic layer segmentation, we determined ganglion cell layer thickness in areas projecting to the side of the retrochiasmal lesion and compared it with ganglion cell layer thickness on the healthy side. Results: We found that retrochiasmal lesions at any level may be associated with an atrophy of ganglion cells. This atrophy respects the vertical midline through the fovea and thus the anatomic separation of the nasal and temporal visual field. The vertical line separating the affected from the unaffected side has significantly less tilt as compared with the disc–fovea angle. Lesions of the optic tract are associated with earlier macular ganglion cell atrophy than retrogeniculate lesions. Macular ganglion cell atrophy may be present in cases with normal peripapillary nerve fiber layer analysis and vice versa. Conclusions: Macular ganglion cell layer thickness shows a topographic hemiatrophy in retrochiasmal lesions, which manifests earlier for tract lesions than for retrogeniculate lesions. This additional examination of ganglion cell homonymous hemiatrophy has a higher sensitivity in detecting retrograde transsynaptic degeneration than the analysis of the peripapillary nerve fiber layer alone.